A systematic review of factors influencing pregnant women's future vaccination choices. (13th November 2019) - Rosso, A; Massimi, A; Adamo, G; Baccolini, V; Pitini, E; Vacchio, M R; Marzuillo, C; De Vito, C; Villari, P
Abstract: Background: Over the last years, vaccine hesitancy has been increasing globally, leading to a decrease in vaccination coverage in several Countries, mostly in Europe. Several systematic reviews were conducted to assess the determinants of hesitancy and of vaccination choices, but none of them focused on pregnant women, which would represent an ideal population to promote correct information on vaccines. Methods: We conducted a systematic review of studies assessing knowledge and attitudes on paediatric vaccinations, vaccination choices and their determinants among pregnant women. We searched Medline, Scopus and Web of Science, adapting search terms to the different databases, following PRISMA Statement criteria. No time limits were set. Results: A total of 5, 309 records were retrieved. After duplicates removal and title/abstract selection, 15 full texts were included in the narrative synthesis. Most studies (14/15) were quantitative surveys, 2 focused only on specific vaccines (rotavirus and HPV), 4 studies were conducted in European countries (Germany and Italy). The main factors associated with vaccine hesitancy or refusal were the fear of side effects, in particular for the most recent vaccines, the perception of a greater importance of natural immunity and a low perception of utility of vaccines, the lack of trust in health professionals, having obtained information on vaccines not from a doctor, primiparity and a low level of education (for these two last factors, with inconsistent results between studies). Conclusions: Available evidence shows that the perceived risks and importance of vaccinations and the information received during pregnancy can influence vaccination choices of future mothers, and that the determinants of hesitancy may vary in different contexts. Pregnant women represent a key population for the implementation of interventions aimed at increasing knowledge and acceptance of vaccinations, which should be based on an analysis of the specific context. Key messages: The perceived risks and importance of vaccinations and the information received during pregnancy can influence vaccination choices of future mothers. Interventions aimed at increasing knowledge and acceptance of vaccinations should be based on an analysis of the specific context.